Letras (Lima): Some lessons towards the centenary - Bolo-Varela, Oswaldo (2022)
The aim of this article is to offer a bibliographical review of the main editions that the journal Letras (Lima) has published since its foundation (1929). To this end, following documentary-methods, we review some of the most important milestones in the trajectory of this journal. First, we look at the first issue of the journal. We review the content published, as well as the imprint it established with its origin. Second, we situate the journal Letras (Lima) within the tradition of academic journals published at the UNMSM in contrast to some nineteenth-century journals and its current situation. Third, we comment on the nature of the thematic issues and how these are a valuable option for future editions of the journal, as well as the changes in the periodization of Letras (Lima). We also comment on the importance of indexing in Scopus and WOS (ESCI) as part of an extensive process of revision, growth, and positioning in the Latin American academy, without neglecting the trajectory of the journal Letras within the Peruvian academic world. Finally, we comment on some of the journal’s recent publications and their achievements, as well as some of the journal’s short and medium-term objectives based on our experience as associate editors.